The exception that proves the rule: female sex offending and the gendered nature of sexual violence - Mary Stathopoulos
This paper explores statistics about the prevalence of female sex offending and outlines the impacts on victims of sex offences by women, as well as issues related to disclosing the abuse. Introduction National and international victimisation data demonstrate that intimate forms of violence, such as domestic and family violence, are gendered. However in both academic and popular discourses there is a lively debate about the possibility of men's and women's equivalent use of physical, emotional and psychological violence, with some researchers arguing that there is no gender difference in the perpetration of intimate partner and domestic violence. The debate centres on the notion that domestic violence is gender neutral - rather than a gendered crime in which men are by and large the perpetrators and women and children make up the majority of victims. This debate can be dangerous as it may promote men's denial of their violence toward women and denial of women's experiences of violent victimisation. Denial can continue the cycle of power and control that is a feature of men's violence against women. While sexual violence has tended not to be a feature of these debates, its gendered nature (as demonstrated by the statistics) is challenged and undermined when instances of female sex offending are reported in the public domain. Like the gender symmetry debate in domestic and family violence, the occurrence of female sex offending is seen to invalidate the empirically supported notion that sexual assault is a gendered crime. It is important therefore to present what is currently known about female sex offenders in an examination of available data. The importance of research on female sexual offending is highlighted by the difficulty in conceptualising it. In the existing research/literature, there is no real clarity around what motivates females to sexually offend. However there is often a rejection of the idea of women having the potential for violence and deviant, coercive sexuality. There is an over-reliance on gender in discussing female sex offenders (specifically in the media and more broadly on a social/cultural level) that can often lead to the notion that female sex offending is less harmful - psychologically and physically - than male sex offending. Gender relates to the social characteristics attributed to men and women that can often be more prescriptive than descriptive of actual characteristics and behaviour. Although gender is an important conceptual tool there may be an over-reliance on gendered stereotypes in the public domain. Conversely, gender may play a role in how men and women sexually offend and ways that gender may conceal women's offending. It is here that the difficulty lies - and a review of the literature does not completely undo this difficulty. Little is known about female sex offenders, and what empirical work has been done is in the initial stages of identifying characteristics associated with female sex offenders. Although prevalence rates are variable, the general consensus is that around 5% of sex offences are committed by women. Much of the work - which began in earnest in the 1980s - has limitations due to being conducted mainly with known offenders who are in the criminal justice system, or with very small clinical samples. Small sample sizes occur because there are only very small populations of female sex offenders, as opposed to much larger populations of male sex offenders. There currently appear to be no research summaries that bring together everything that is known about female sex offenders. This Research Summary will explore the current literature - predominantly from 2000 onward - and outline what is currently known about female sex offenders. Tables of data related to offence and offender characteristics will be presented to bring together the current available empirical evidence. The impacts on victims and issues related to disclosing sexual abuse perpetrated by women are also included